Development of Volunteer International Craniofacial Surgery Missions. Issue 4 (June 2015) - Taub, Peter James; Lin, Alexander Y.; Cladis, Franklyn P.; Baker, Stephen B.; Gooden, Cheryl K.; Kumar, Anand; Losee, Joseph E.; Menard, Robert; Starks, Red; Duncan, John A.; De Pawlikowski, Wieslawa; Cecchi, Andres Wiegering; et al.
<x xml:space="preserve">Abstract</x> Abstract Volunteer surgical missions to provide cleft care to patients in developing countries has been done successfully for a number of years. Similar missions that provide craniofacial surgery introduce a dramatic step up in complexity. While articles have addressed protocols for the safe delivery of cleft care around the world, little has been written on volunteer craniofacial surgical missions. Komedyplast was established in March 2001 as a 501c(3) nonprofit organization to provide craniofacial surgical care to underserved populations and educate local surgeons in craniofacial principles. During 9 annual missions, the organization has provided surgical care to more than 150 patients with various complex, congenital, craniofacial conditions. The article addresses important safeguards that have been implemented to maximize safety and minimize risk.